Apakah durasi latihan dan fase siklus menstruasi mempengaruhi performa atlet futsal wanita? Perspektif survei kritis - Supriadi, Dedi (Universitas Nusantara PGRI Kediri, 2023)
The menstrual cycle phase and the duration of practice often interfere with female futsal athletes' performance during training. This study explores the relationship between exercise duration, menstrual disorder and the performance of women’s futsal athletes. This research method uses a survey. The subjects of this study were 22 female futsal athletes in the city of Cimahi. The instrument was a closed interview validated by a women's soccer expert (coach of the Indonesian women's soccer team) from STKIP Pasundan and tested on three participants who met the inclusion criteria. Descriptive analysis is presented as the mean and differences between groups were evaluated by t-test with a statistically significant level of p < 0.05. Descriptive analysis using SPSS software (version 21.0). This study reveals that the significance test with sig.0.13 <0.05 on the duration variable, which means that the exercise's duration directly affects the athlete's performance. In comparison, the menstrual cycle variable has a sig.0.91 value > 0.05, which means that the menstrual cycle does not directly affect the performance of female futsal athletes. However, the significant results showed no effect of the menstrual cycle on the performance of female futsal athletes. This study recommends that female futsal coaches pay attention to the duration of training during the menstrual period for each athlete to achieve optimal performance.